Serum Fetuin-A and Insulin Levels in Classic Congenital Adrenal Hyperplasia - Kurnaz, Erdal; Çetinkaya, Semra; Özalkak, Şervan; Bayramoğlu, Elvan; Demirci, Gülşah; Öztürk, Hasan Serdar; Erdeve, Şenay Savaş; Aycan, Zehra (Hormone and Metabolic Research, 2020)
Androgens play a pivotal role in non-reproductive organs such as the kidney, heart, liver, and pancreas. As androgen receptors are expressed in pancreatic and liver cells, excess testosterone can result in hypersecretion of insulin and fetuin-A, a protein produced in the liver. The expression of fetuin-A, a natural inhibitor of tyrosine kinase activity in muscle and liver, leads to insulin resistance. In addition, insulin and fetuin-A levels are thought to be affected by drugs such as glucocorticoids (GCs) and fludrocortisone. However, whether fetuin-A and insulin levels are affected by androgens and GCs in patients with classic congenital adrenal hyperplasia (CAH) is unknown. This cross-sectional study included 56 CAH patients and 70 controls. Analyses were stratified by sex and prepubertal/pubertal status to control for potential changes in serum metabolic/inflammatory markers associated with the production of sex steroids. Fasting blood glucose, insulin, triglyceride, total cholesterol, high density lipoprotein-cholesterol, aspartate aminotransferase, alanine aminotransferase, fetuin-A, and high-sensitivity C-reactive protein (hs-CRP) levels were measured in blood samples. In addition, 17α-hydroxyprogesterone, androstenedione, total testosterone, free testosterone, and dehydroepiandrosterone sulfate levels were measured before medication was administered. Insulin and fetuin-A levels were significantly higher in CAH patients than in controls. The unfavourably high levels of these substances exhibited a positive correlation with total and free testosterone. Regression analysis revealed that fetuin-A and free testosterone were the only independent predictors of the insulin level, while insulin and free testosterone levels significantly predicted the fetuin-A level (R2=42.7% and 59.8%). Differences were also observed in triglyceride and hs-CRP levels between the pubertal and prepubertal groups. We conclude that serum fetuin-A and insulin levels may be associated with androgens in CAH patients.
Keywords: congenital adrenal hyperplasia; fetuin-A; alpha-2-HS-glycoprotein; insulin resistance